Identification and validation of neurotrophic factor-related gene signatures in glioblastoma and Parkinson’s disease - Zhao, Songyun; Chi, Hao; Yang, Qian; Chen, Shi; Wu, Chenxi; Lai, Guichuan; Xu, Ke; Su, Ke; Luo, Honghao; Peng, Gaoge; Xia, Zhijia; Cheng, Chao; et al. (Frontiers in Immunology, 2023)
Glioblastoma multiforme (GBM) is one of the most common malignancies of the central nervous system, and Parkinson's disease (PD) is a degenerative neurological disease commonly seen in the elderly. Neurotrophic factors have long been thought to play an important role in the development of degenerative neuropathies and gliomas. Through machine learning algorithms and validation of two external cohorts, we identified 4 NFRGs as more accurate for the diagnosis of Parkinson's disease course. Meanwhile, 7 NFRGs were considered to be closely related to the prognosis of GBM and were good predictors of GBM. the NFRGs signature was an independent prognostic factor for GBM, patients in the low-risk group had a higher overall survival (OS) than those in the high-risk group, and the nomogram constructed from clinical features and risk scores had good predictive power for prognosis. The low-risk group was more likely to benefit from immunotherapy by the degree of immune cell infiltration, the level of immune checkpoint expression, and the predicted outcome of multiple immunotherapy efficacy. Ultimately two NFRGs, EN1 and LOXL1, are thought to play an important role in the progression of Parkinson's disease and the prognosis of GBM. In conclusion, our study revealed that 4 NFRGs intervene in the progression of PD. Based on the 7-NFRGs risk score model can well predict the prognosis of GBM patients and help clinicians to classify the prognosis of GBM patients. Targeting two biological targets, EN1, and LOXL1 allows for personalized immunotherapy for patients with PD and GBM.